2023
DOI: 10.1088/1755-1315/1165/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed priming on growth and physiological responses of chili pepper (Capsicum frutescens L.) under salinity stress

Abstract: Increasing soil salinity in some agricultural areas due to global climate change is an obstacle in horticultural crop cultivation. Chili pepper (Capsicum frutescens L.) is an important horticultural crop that has high economic values but the extensive cultivation in saline land can reduce yields. Plant tolerance must be increased to be able to adapt in salinity stress conditions. One method that can be used is seed priming, which is pre-soaking the seeds to increase germination under unfavourable conditions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Genetic variances, seed coat thickness, and internal porosity may all contribute to the variability in water absorption across cultivars. Their internal porosity can in uence the water absorption index in seeds [15]. A higher water absorption index cultivar may have improved permeability or structural characteristics that enable effective water uptake [11].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variances, seed coat thickness, and internal porosity may all contribute to the variability in water absorption across cultivars. Their internal porosity can in uence the water absorption index in seeds [15]. A higher water absorption index cultivar may have improved permeability or structural characteristics that enable effective water uptake [11].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the literature on the synthesis of proline in stress conditions are controversial. For example, an increase in proline has been observed in many studies on primed plants exposed to stress [29,71,72,79]; vice versa, some authors [80,81] found no change in the production of this osmolyte in stressed plants. In our study, no proline accumulation was observed in the primed stressed plants.…”
Section: Activation Of Signaling and Salt Tolerance Responsesmentioning
confidence: 98%